Reducing production costs using the Activity-based Cost Accounting System (ABC) Case Study of The Great Mills Corporation for the South in Biskra - Mkhalkhal, Zwina (Finance and Business Economies Review, 2020)
the aims of our study is to present the activities-based cost accounting system (ABC), which is one of the most important modern methods used in enterprises with the aim of minimizing the cost of production and this is done by allocating indirect expenses for each activity that contributes to the construction of the product on Reverse traditional methods that rely on the principle of relying on a fixed rate in the allocation of indirect expenses. Therefore, in this study, we will try to project the theoretical aspect of the field reality of the Great Mills Foundation of the South with a precision unit and a free for fiscal year 2018.